Dimensions of aging and their influence on physical activity = Wymiary starzenia i ich wpływ na aktywność fizyczną - Podhorecka, M.; Główczewska, J.; Ciesielska, N.; Gębka, D.; Sokołowski, R.; Szymańska, A.; Jagielski, D.; Zukow, W. (Journal of Education, Health and Sport, 2015)
Podhorecka M., Główczewska J., Ciesielska N., Gębka D., Sokołowski R., Szymańska A., Jagielski D., Zukow W. Dimensions of aging and their influence on physical activity = Wymiary starzenia i ich wpływ na aktywność fizyczną. Journal of Education, Health and Sport. 2015;5(12):230-239. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.35365 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2812%29%3A230-239 http://pbn.nauka.gov.pl/works/680050 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 10.11.2015. Revised 25.11.2015. Accepted: 14.12.2015. Dimensions of aging and their influence on physical activity Wymiary starzenia i ich wpływ na aktywność fizyczną M. Podhorecka1, J. Główczewska1, N. Ciesielska1, D. Gębka1, R. Sokołowski2, A. Szymańska1, D. Jagielski1, W. Zukow3 1Katedra i Klinika Geriatrii, Collegium Medicum UMK, Toruń, Bydgoszcz, Polska/ Nicolaus Copernicus University in Toruń, Collegium Medicum in Bydgoszcz, Department of Geriatrics, Poland 2Katedra Higieny, Epidemiologii i Ergonomii , Collegium Medicum UMK, Toruń, Bydgoszcz, Polska/ Nicolaus Copernicus University in Toruń, Collegium Medicum in Bydgoszcz, Department of Hygiene and Epidemiology, Poland 3Wydział Kultury Fizycznej, Zdrowia i Turystyki, Uniwersytet Kazimierza Wielkiego w Bydgoszczy, Polska/ Faculty of Physical Education, Health and Tourism, Kazimierz Wielki University, Bydgoszcz, Poland Abstract Old age is a common and a universal phenomenon. It is difficult to define the beginning of the process of aging and entering the period of late adulthood. As time passes, the symptoms of aging become more and more visible. The work presents three dimensions of aging: biological, psychological and social. It demonstrates their influence on physical activity. It shows barriers the elderly people need to overcome or the situations they might be in. It also shows physical activity as one of the main components of the activation process of the elderly. Key words: elderly, physical activity, aging.